Dysbiosis of human tumor microbiome and aberrant residence of Actinomyces in tumor-associated fibroblasts in young-onset colorectal cancer - Xu, Zhuoqing; Lv, Zeping; Chen, Fangqian; Zhang, Yuchen; Xu, Zifeng; Huo, Jianting; Liu, Wangyi; Yu, Suyue; Tuersun, Abudumaimaitijiang; Zhao, Jingkun; Zong, Yaping; Shen, Xiaonan; et al. (Frontiers in Immunology, 2022)
Colorectal cancer (CRC) is the third most common form of cancer, and the incidence of sporadic young-onset colorectal cancer (yCRC) has been increasing. Microbiota residing in the tumor microenvironment are emerging tumor components. The colonic microbiome differs between patients with CRC and healthy controls; however, few studies have investigated the role of the tumor microbiota in disease diagnosis and tumorigenesis of yCRC. We performed 16S rRNA sequencing analysis to identify the microbiome in CRC and found that tumor microbial diversity decreased in yCRC. Proteobacteria and Firmicutes were the most abundant phyla in all CRC samples, and Actinomyces and Schaalia cardiffensis were the key microbiota in the yCRC group. Correlation analysis revealed that Actinomyces co-occurred with various pro-tumor microbial taxa, including Bacteroidia, Gammaproteobacteria, and Pseudomonas. An independent cohort was used to validate the results. The Actinomyces in CRC was co-localized with cancer-associated fibroblasts, and activated the TLR2/NF-κB pathway and reduces CD8+ T lymphocyte infiltration in CRC microenvironment. This study suggests that tumoral microbiota plays an important role in promoting tumorigenesis and therefore has potential as a promising non-invasive tool and intervention target for anti-tumor therapy.